Facilitators and Barriers of Bystander Intervention Intent in Image-Based Sexual Abuse Contexts: A Focus Group Study with a University Sample - Mainwaring, Chelsea (Journal of interpersonal violence, 2024)
Image-based sexual abuse (IBSA) encompasses the taking, sharing, and/or threatening to share nude or sexual images of others without their consent. The prevalence of IBSA is growing rapidly due to technological advancements, such as access to smartphones, that have made engagement in such activities easier. Bystanders offer an important means of intervention, but little is known about what facilitates or inhibits bystander action in these contexts. To address this gap in the literature, seven focus groups (n = 35) were conducted to explore the factors that facilitate and inhibit bystander action in the context of three different IBSA scenarios (taking, sharing, and making threats to share nude or sexual images without consent). Using thematic analysis, eight themes were identified, suggesting that the perceived likelihood of intervention increased with greater feelings of responsibility, empathy with the victim, reduced feelings of audience inhibition, greater feelings of safety, greater anger toward the IBSA behavior, closer relationships with the victim and perpetrator, the incident involving a female victim and male perpetrator, and perception of greater benefits of police involvement. These findings are considered alongside the physical sexual violence literature in highlighting the similarities and nuances across the different contexts. Implications for the development of policies and educational materials are discussed in relation to encouraging greater bystander intervention in IBSA contexts.